Effect of Facilitated Tucking on Physiological and Behavioural Responses to Pain among Infants Receiving Vaccination - Mercy Joseph1, Reshma K. Sasi1, Alphonsa Michael2, Amrutha C.2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: To evaluate the effect of facilitated tucking on physiological and behavioural responses to painamong infants between experimental and control group before and after the IM vaccinationMethod: A quantitative approach with true experimental design and consecutive sampling technique wasused in this study. Researcher selected 100 infants up to the age of 6 month receiving IM vaccination inthe immunization clinic, AIMS, Kochi, and they are randomly assigned to control and experimental group.Demographic and clinical data was collected using structured interview schedule. Heart rate and SPO2was monitored 2 minutes prior to the vaccination and facilitated tucking was given to the experimentalgroup before and during the immunization and routine position was given to the control group, after thatbehavioural response was assessed by using neonatal infant pain scale and physiological response such asheart rate and SPO2 was assessed after 5 minutes.Result: The result showed that all the subjects in the control group had severe pain 100 %, whereas in theexperimental group 50 % of the subjects had moderate pain and 50% of them had mild pain. Also there wasa significant difference in the mean score of the physiological and behavioural response between the controland experimental group after the interventionConclusion: The study revealed that the Facilitated Tucking improves the emotional security and reducesthe pain perception. The nurse or care givers can effectively implement facilitative tucking for reducing painduring vaccination in any setting as it is a very simple technique